KUALITAS PELAYANAN PEMBUATAN PASPOR DI KANTOR IMIGRASI KELAS I KOTA BOGOR - Bintari, Suciani Cahya; S.Zenju, Nandang; Purnamasari, Irma (JURNAL GOVERNANSI, 2017)
The purpose of this study is to determine the passport service quality at Class I Immigration Office of Bogor.The theory used in this research is put forward by Parasuraman, Berry and Zeithaml (Ratminto & Septi Winarsih, 2005: 175), which consists of five dimensions of service quality : Tangible, Reliability, Responsiveness, Assurance and Empathy. The method used is descriptive analysis using quantitative approach. Data analysis technique used is the calculation of Weight Mean Score (WMS). Data collection techniques used are literature studies and field studies. The study population consists of 220 respondents consisting of Applicants and Passport Officers. While the sampling technique used is the saturated technique sampling to officers and incidental sampling to the applicants. The samples using Yamane formula so that the samples obtained are 87 respondents.Research result of service quality in making passport at Bogor immigration office is considered to be good, because of the processing of a questionnaire made to the applicants passport 67 samples obtained is score of 3.67 (in scale of 5), which is included in the âgoodâ category. Nevertheless there are many grievances felt by the applicant. This occurs due to less extent of the lounge to the applicant, the speed of completing the passport, guarantee timely completion of the passport, and the discriminatory treatment which actually is for the elderly, toddlers, pregnant and breastfeeding.Â Keywords: Service Quality, Five Dimension of Service Quality, Passport.